The Chloroplastic Small Heat Shock Protein Gene KvHSP26 Is Induced by Various Abiotic Stresses in Kosteletzkya virginica - Xiaohua Liu; Lizi Zhao; Jianzhao Li; Lijun Duan; Kai Zhang; Xuqiang Qiao; Weihuan Li; Chengchao Zheng; Xiaoli Tang; Hongxia Zhang (International Journal of Genomics)
Small heat shock proteins (sHSPs) are a group of chaperone proteins existed in all organisms. The functions of sHSPs in heat and abiotic stress responses in many glycophyte plants have been studied. However, their possible roles in halophyte plants are still largely known. In this work, a putative sHSP gene KvHSP26 was cloned from K. virginica. Bioinformatics analyses revealed that KvHSP26 encoded a chloroplastic protein with the typical features of sHSPs. Amino acid sequence alignment and phylogenetic analysis demonstrated that KvHSP26 shared 30%-77% homology with other sHSPs from Arabidopsis, cotton, durian, salvia, and soybean. Quantitative real-time PCR (qPCR) assays exhibited that KvHSP26 was constitutively expressed in different tissues such as leaves, stems, and roots, with a relatively higher expression in leaves. Furthermore, expression of KvHSP26 was strongly induced by salt, heat, osmotic stress, and ABA in K. virginica. All these results suggest that KvHSP26 encodes a new sHSP, which is involved in multiple abiotic stress responses in K. virginica, and it has a great potential to be used as a candidate gene for the breeding of plants with improved tolerances to various abiotic stresses.